Fractal Antennas : A Novel Miniaturization Technique for wireless Networks - REHA, Abdelati; EL AMRI, Abdelkebir; BENHMAMMOUCH, Othmane; OULAD SAID, Ahmed (Discoveries in Agriculture and Food Sciences, 2014)
In the recent years and with the multiplication and miniaturization of telecommunications systems and their integration in restricted environments, such as Smart-phones, tablets, cars, airplanes, and other embedded systems. The design of compact multi-bands and Ultra Wide Band (UWB) antennas becomes a necessity. One of the interesting techniques to provide this kind of antenna is the use of fractal structures.